2014
DOI: 10.1186/2193-1801-3-721
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics of SALL4-immunopositive hepatocellular carcinoma

Abstract: The aim of this study was to investigate the clinicopathologic characteristics of sal-like protein 4 (SALL4)-immunopositive hepatocellular carcinoma (HCC). Solitary HCCs that were surgically treated at the University of Tokyo Hospital between 2000 and 2008 were the subject of this study. Diffuse, non-punctate nuclear immunoreactivity to SALL4 was observed in 47 of 337 HCCs (13.9%). Compared to patients with SALL4-negative HCC, patients with SALL4-positive HCC were younger (mean 59.2 years vs. 65.2 years), more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…In the present study, we also found that SALL4 was significantly upregulated in HCC tissues and cell lines, when compared to their matched adjacent normal tissues and normal liver cell line, respectively. Our data are consistent with those of previous studies (11,29,30). Moreover, in this study, to the best of our knowledge, we demonstrated for the first time that the overexpression of SALL4 reversed the suppressive effects of miR-33b overexpression on HCC cell proliferation, migration and invasion, indicating that SALL4 is involved in the miR-33b-meditated malignant phenotypes of HCC cells.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we also found that SALL4 was significantly upregulated in HCC tissues and cell lines, when compared to their matched adjacent normal tissues and normal liver cell line, respectively. Our data are consistent with those of previous studies (11,29,30). Moreover, in this study, to the best of our knowledge, we demonstrated for the first time that the overexpression of SALL4 reversed the suppressive effects of miR-33b overexpression on HCC cell proliferation, migration and invasion, indicating that SALL4 is involved in the miR-33b-meditated malignant phenotypes of HCC cells.…”
Section: Discussionsupporting
confidence: 93%
“…For the cancer recurrence, considering the available 4 studies [16, 23, 25, 28] and the 17 TCGA cohorts, a similar result was obtained confirming a worse prognostic role of SALL4+ (HR=1.52; 95% CI: 1.22-1.89, p=0.0002; I 2 =69%) (Figure 2b). …”
Section: Resultssupporting
confidence: 67%
“…These HCCs tend to be more aggressive and associated with a poor prognosis 68 . Compared to SALL4-negative cases, HCC patients with SALL4 expression show higher frequency of tumor cell invasion, intrahepatic metastasis, and are positive for cytokeratin 19 and Epithelial Cell Adhesion Molecule (EpCAM), as well as other cancer stem cell markers 112 . A positive correlation between SALL4 and EpCAM expression have been reported in other HCC studies 91113114115 .…”
Section: Sall4 In Cancersmentioning
confidence: 99%